Factors Related to the Severity of COVID-19 Pneumonia Among Thai Patients in Community Hospitals of Nakhon Si Thammarat Province - Chooprasoot, Thittita; Noonil, Naiyana; Jantasuwan, Rachadaporn; Songprasert, Thanawan (Science, Technology, and Social Sciences Procedia, 2025)
Coronavirus Disease 2019 (COVID-19) pneumonia remains a significant cause of morbidity in hospitalized patients, particularly among vulnerable populations. This study aimed to determine the prevalence of respiratory failure and to identify factors associated with the severity of COVID-19 pneumonia among patients admitted to community hospitals in Nakhon Si Thammarat Province, Thailand. A retrospective cross-sectional study was conducted among 356 patients diagnosed with COVID-19-related pneumonia and admitted to Thung Song and Tha Sala Hospitals between July 1, 2022, and June 30, 2024. Participants were selected based on specific inclusion criteria. Data were collected using structured forms that captured demographic information, comorbidities, and clinical records. Descriptive statistics, the Chi-square test, and Fisher’s exact test were used for data analysis. The prevalence of respiratory failure among hospitalized COVID-19 pneumonia patients was 29 %. Most patients were female (66.3 %) and aged ≥ 60 years (65.7 %). A total of 28.9 % of patients were classified as overweight or obese (BMI ≥ 25 kg/m²). The most common comorbidities included hypertension (44.9 %), diabetes mellitus (14.9 %), and chronic respiratory disease (4.2%). Factors significantly associated with severe COVID-19 pneumonia included advanced age, alcohol consumption, and length of hospital stay (p < 0.05). Therefore, older adults, individuals with chronic conditions (e.g., hypertension, diabetes, chronic respiratory diseases), and those who consume alcohol are at elevated risk for severe COVID-19 pneumonia. Targeted surveillance and clinical management strategies should prioritize these high-risk groups to reduce adverse outcomes.